In vitro antidermatophytic activity and cytotoxicity of extracts derived from medicinal plants and marine algae - Sit, Nam Weng; Chan, Yik Sin; Lai, S.C.; Lim, Lay Ngor; Looi, G.T.; Tay, P.L.; Tee, Y.T.; Woon, Y.Y.; Khoo, Kong Soo; Ong, Hean Chooi (Elsevier Masson, 2018)
Objectives: This study was conducted to evaluate the antidermatophytic activity of 48 extracts obtained from medicinal plants (Cibotium barometz, Melastoma malabathricum, Meuhlenbeckia platyclada, Rhapis excelsa, Syzygium myrtifolium, Vernonia amygdalina) and marine algae (Caulerpa sertularioides, Kappaphycus alvarezii) against Trichophyton rubrum and Trichophyton interdigitale (ATCC reference strains), and the cytotoxicity using African monkey kidney epithelial (Vero) cells. Active plant extracts were screened for the presence of phytochemicals and tested against clinical isolates of Trichophyton tonsurans. Methods: Six different extracts (hexane, chloroform, ethyl acetate, ethanol, methanol and water) were obtained from each plant or algae sample using sequential solvent extraction. The antidermatophytic activity for the extracts was assessed using a colourimetric broth microdilution method. The viability of Vero cells was measured by Neutral Red uptake assay. Results: All the extracts (except the water extracts of V. amygdalina, C. sertularioides and K. alvarezii) showed antidermatophytic activity against Trichophyton spp. The minimum fungicidal concentration (MFC) ranges for the plant extracts against T. rubrum and T. interdigitale are 0.0025–2.50 and 0.005–2.50 mg/mL, respectively. The algae extracts exhibited lower potency against both species, showing MFC ranges of 0.08–2.50 and 0.31–2.50 mg/mL, respectively. The ethanol and methanol extracts from the leaves of R. excelsa, and the methanol and water extracts from the leaves of S. myrtifolium were highly active (MFC < 0.1 mg/mL) and with high selectivity indices (SI > 2.8) against reference strains of T. rubrum and T. interdigitale, and most of the clinical isolates of T. tonsurans. Phytochemical analysis indicates the presence of alkaloids, anthraquinones, flavonoids, saponins, tannins, phenolics and triterpenoids in the extracts. Conclusions: The medicinal plant extracts exhibited stronger antidermatophytic activity compared to the algae extracts. The leaves of R. excelsa and S. myrtifolium are potential sources of new antidermatophytic agents against Trichophyton spp.